Formation of Arbitrary Patterns in Ultraviolet Cured Polymer Film via Electrohydrodynamic Patterning - Xin Li; Yucheng Ding; Jinyou Shao; Hongmiao Tian; Hongzhong Liu (The Scientific World Journal)
Electrohydrodynamic patterning of arbitrary patterns is achieved by optimizing the critical parameters (applied voltage and spacer height). The applied voltage has a great influence on the fidelity of L-shaped line structures with different sizes. The L-shaped line structures with high fidelity are obtained by using the moderate applied voltage. The spacer height has a great influence on the fidelity of square structures with different sizes. The square structures with high fidelity are obtained by using the low height spacer. The multi-field coupling transient finite element simulation demonstrates that the lack of polymer owing to the high height spacer leads to the formation of defects.